Shared decision making in perioperative medicine. (2nd April 2020) - Timbrell, David; Santhirapala, Ramai
Abstract : Shared decision making is a collaborative process between clinicians and patients, which aims to select the most suitable management option based on both best available evidence and patient preferences. This article looks at the role of shared decision making in perioperative medicine.